Family caregiver support—a facilitator to empower family caregivers. (3rd August 2021) - Fernandes, Sílvia; Portugal, Paula; Mullins, Lhara; Power, Martin; Letica-Crepulja, Marina; Stevanović, Aleksandra; Frančišković, Tanja; Silva, Regina A
Abstract: Background: Mental disorders are highly prevalent, placing an enormous burden on individuals, society and economy. Research shows that family members who provide care to individuals with chronic or disabling mental conditions are themselves at risk. As a response to this problem, the project 'Family Caregiver Support - Strategies and tools to promote the mental and emotional health of caregivers' emerged, funded by Erasmus + Program and carried out by 8 European partners including ESS|P.PORTO. Objectives: To empower family members as caregivers and to give them access to relevant medical information and to psychological support for their own needs. Methods: A Guide and a Resource Pack concerning 9 important mental health disorders were developed. An interactive e-platform and a mobile App were developed to make available these materials. Validation of the products was carried out, in each country, by caregivers and health/social care professionals through online questionnaires. Data were collected and processed in an anonymous manner, and the confidentiality was ensured. Results: In Portugal, 98% of respondents (25 caregivers/citizens interested on subject, and 25 health/social care professionals), consider the accessibility and attractivity of the platform very good or excellent; and more than 90% consider materials very effective for the caregiver's empowerment. Some issues were identified to add to Resource Pack. Conclusions: Data from partners is being processed but there is already strong evidence of the usability and efficacy of the project's outcome, and a strong contribution was done for adult education concerning physical, mental and emotional health promotion of family caregivers.